Since 1948 : Israeli literature in the making - Berg, Nancy E.; Sokoloff, Naomi B. (SUNY series in contemporary Jewish literature and culture., 2020)
"Argues for stretching the boundaries of Israeli literature linguistically, geographically, and generically"--